Satellite-based solar energy potential analysis for southern states of India - Deepak Kumar (Energy Reports, 2020)
Numerous efforts have been taken to exhibit scientific advancement in solar energy analysis. The current study attempts to demonstrate an approach for the solar resource variability analysis at a spatial scale in the southern states of India. This work utilized the satellite-derived modelled solar insolation datasets due to the global unavailability of in-situ meteorological data sets (especially solar radiation data). The visualization of solar insolation components including direct normal irradiance (DNI) and global horizontal irradiance (GHI) provided an opportunity to understand the energy configurations and it's potential. An average DNI variation of 5.21 kWh/m2 and GHI variation of 5.72 kWh/m2 was observed. The ancillary analysis presented a detailed map for southern states of India at a grid resolution of 100 km x 100 km. Thereafter DNI and GHI distribution map for selected random points were estimated. The precise summary statistics stated that maximum and minimum values of DNI range from 3.72 kWh/m2 to 5.59 kWh/m2 with an average value of 5.18 kWh/m2 and likewise maximum and minimum values of GHI ranges from 4.91 kWh/m2 to 5.99 kWh/m2 with an average value of 5.71 kWh/m2. It was observed that the states of Karnataka and Tamil Nadu have a better prospect for further applications. The obtained results provided datasets for further analysis to comprehend the spatial distribution at a regional or national level. These will be very much useful for better energy planning for sound decision making.
Keywords: 330; Clean energy systems; Direct normal irradiance (DNI) & global horizontal irradiance (GHI); Solar energy potential analysis; Solar insolation